Natural products and botanical medicines of Iran - Owfi, Reza (Boca Raton : CRC Press, 2021)
With a high diversity of vegetation in Iran, over 8000 plant species are in existence. More than 2300 species of these plants have medicinal, edible and industrial properties, and more than 1700 species of them are endemic. Natural Products and Botanical Medicines of Iran provides an overview on important endemic plants and their usages. All results have been tabulated and key detailed information of each species is presented with background data. Features: Provides an understanding of indigenous plant-derived natural medicines of the most important medicinal plants in the region Includes discussions and critical views on the potentials and challenges for further development of the selected plants in a modern setting Details the important plants and sets out the chapters based on either taxonomy or medical use
OCLC-licensed vendor bibliographic record.
Keywords: Medicinal plants -- Iran; Materia medica, Vegetable -- Iran; Herbs -- Therapeutic use -- Iran; Botany, Medical -- Iran; SCIENCE / Chemistry / Organic; MEDICAL / Pharmacology